DECENTRALIZATION OR CENTRALIZATION - THE ASYMMETRY OF LOCAL SELF-GOVERNMENT IN GEORGIA (Lex localis - Journal of Local Self-Government, 2025)
The effective implementation of state governance is directly proportional to the proper and efficient functioning of local self-government. The territorial division of a state is usually based on historical and geographical foundations, although under contemporary conditions other factors may also influence the alteration of administrative borders. Georgia is a small country, constitutionally a unitary state, yet with three autonomous entities which, on several occasions, have posed threats to the unity of Georgian statehood. Moreover, today Georgia’s temporarily lost territories - the Autonomous Republic of Abkhazia and the Autonomous Region of Ossetia - continue to present serious challenges for the country. Against this backdrop, Georgia constantly faces a critical question: should it lean toward full decentralization, which implies granting extensive powers to local self-governments, or toward strict centralization, since a small, unitary country may not require wide distribution of power among local units?The article “Decentralization or Centralization - The Asymmetry of Local Self-Government in Georgia” focuses on this fundamental dilemma confronting the system of public administration in modern Georgia: whether to advance decentralization mechanisms or to maintain a strong centralized governance model that could help overcome the asymmetry currently evident in local self-governments. The research draws on both historical- political  experience  and  the  existing  legislative  framework  and  institutional  practice. Special emphasis is placed on the problem of asymmetry, expressed in the unequal capacities of local self- governments in terms of financial, administrative, and political resources. It is evident that the capabilities of self-governing units vary significantly across Georgian regions: in some cases municipalities remain heavily dependent on the central government, while in others they are able to make relatively autonomous decisions. This asymmetry complicates the establishment of a unified and equitable development strategy.